2019
DOI: 10.56093/ijas.v89i9.93486
|View full text |Cite
|
Sign up to set email alerts
|

Fodder productivity and profitability of different maize and legume intercropping systems

Abstract: The current trend in global agriculture is to search for highly productive, sustainable and eco-friendly cropping systems. Intercropping of cereals with legumes is a recognized practice for economizing the use of nitrogenous fertilizers and increasing the productivity, quality, and profitability particularly in commercial grain crops but possibilities of fodder production in these intercropping systems is less explored. Availability of green fodder with improved quality to animals is the key to success of dair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 4 publications
(2 reference statements)
1
3
0
Order By: Relevance
“…As the crop advanced leaf portion gets decreased and increases the stem potion reflected in lower Leafstem ratio at dent stage of harvest as compared to the milky and soft dough stage. These results are in line with the findings of Ginwal et al [10] and Rathod et al [11].…”
Section: Leaf-stem Ratiosupporting
confidence: 93%
“…As the crop advanced leaf portion gets decreased and increases the stem potion reflected in lower Leafstem ratio at dent stage of harvest as compared to the milky and soft dough stage. These results are in line with the findings of Ginwal et al [10] and Rathod et al [11].…”
Section: Leaf-stem Ratiosupporting
confidence: 93%
“…It was found that all maize based cropping combinations had higher values for N content of the soil over sole treatment of maize. Similar results were obtained by Ginwal et al (2019). Fodder crops in Kashmir…”
Section: Fig 2: Dry Fodder Yield Of Maize and Legumes In Different Co...supporting
confidence: 86%
“…Moreover, additional P is essential for increasing biomass. The beneficial effects of P addition promoted legumes to fix more atmospheric nitrogen and increased the productivity of the inter-crops utilized in photosynthesis, which resulted in maximum forage yield [30,31]. Consequently, common vetch/rape intercropping, when P was provided in a reasonable amount, facilitated the production of desirable forages, which contributes to livestock production.…”
Section: Discussionmentioning
confidence: 99%